Energy loss straggling in Aluminium foils for Li and C ions in fractional energy loss limits (ΔE/E) ∼10–60%. (February 2016) - Diwan, P.K.; Kumar, Sunil; Kumar, Shyam; Sharma, V.; Khan, S.A.; Avasthi, D.K.
Abstract: The energy loss straggling of Li and C ions in Al foils of various thicknesses has been measured, within the fractional energy loss limit (∆ E / E ) ∼ 10–60%. These measurements have been performed using the 15UD Pelletron accelerator facility available at Inter University Accelerator Centre (IUAC), New Delhi, India. The measured straggling values have been compared with the corresponding predicted values adopting popularly used collisional straggling formulations viz Bohr, Lindhard and Scharff, Bethe–Livingston, Titeica. In addition, the experimental data has been compared to the Yang et al. empirical formula and Close Form Model, recently proposed by Montanari et al. The straggling values derived by Titeica theory were found to be in better agreement with the measured values as compared to other straggling formulations. The charge-exchange straggling component has been estimated from the measured data based on Titeica's theory. Finally, a function of the ion effective charge and the energy loss fraction within the target has been fitted to the latter straggling component. Highlights: Measured energy loss straggling values are compared with the theoretical predictions. Titeica theory is recognized as a best collisional straggling theory. A fitted relation for charge-exchange straggling is developed.